2020
DOI: 10.1080/15257770.2020.1764971
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of oligodeoxyribonucleotides containing a tricyclic thio analogue of O6-methylguanine and their recognition by MGMT and Atl1

Abstract: Promutagenic O 6-alkylguanine adducts in DNA are repaired in humans by O 6-methylguanine-DNA-methyltransferase (MGMT) in an irreversible reaction. Here we describe the synthesis of a phosphoramidite that allows the preparation of oligodeoxyribonucleotides (ODNs) containing a novel tricyclic thio analogue of O 6-methylguanine in which the third ring bridges the 6-thio group and C7 of a 7-deazapurine. These ODNs are very poor substrates for MGMT and poorly recognised by the alkyltransferase-like protein, Atl1. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…O-6-methylguanine-DNA methyltransferase (MGMT) is a type of suicide DNA damage repair enzymes, and DNA damage repair disorders have been reported to induce autophagy (Balvers et al, 2015;Abdu et al, 2020). Lei et al (2020) have found that the high expression of MGMT is significantly correlated with the low expression of ATG4B and the favorable prognosis of gastric cancer.…”
Section: Regulatory Proteins Inhibiting Both Autophagy and Chemoresismentioning
confidence: 99%
“…O-6-methylguanine-DNA methyltransferase (MGMT) is a type of suicide DNA damage repair enzymes, and DNA damage repair disorders have been reported to induce autophagy (Balvers et al, 2015;Abdu et al, 2020). Lei et al (2020) have found that the high expression of MGMT is significantly correlated with the low expression of ATG4B and the favorable prognosis of gastric cancer.…”
Section: Regulatory Proteins Inhibiting Both Autophagy and Chemoresismentioning
confidence: 99%